ANALYSIS OF YELLOWFIN TUNA (Thunnus albacares) FISHING GROUND BASED ON SEA SURFACE TEMPERATURE AND CHLOROPHYLL-A IN THE WEST SUMATERA WATERS - Habibullah, Ridwan; Mubarak, Mubarak; Galib, Musrifin (Asian Journal of Aquatic Sciences, 2020)
This research was conducted on September 2019 in west Sumatera waters which was aimed to find out the level of aquatic productivity, to analyze the yellowfin tuna fishing ground and to find out the corelation between sea surface temperature (SST) and chlorophyll-a with the total catch of yellowfin tuna. In conducting the research, survey and spatial analyze were used as the method. The highest total catch of yellowfin tuna was on October 2019 with the total 60.610 kg and the CPUE 166 kg/trip. On the other hand, the lowest total catch was on June with the total 18.080 kg and CPUE 92,7179 kg/trip. Based on the result of the CPUE, October is the best month for fishing. The correlation coefficient between SST and total catch in 2018 was -0.69 which mean there was a negative correlation. Meanwhile, the correlation chlorophyll-a with the total catch was 0.65 which mean the corelation between both variables were not good.